Simulation Case Studies on New Approaches to Energy Safeguarding: Empowering Remote Areas with Sustainable Power - E-Alam M.N.; Islam M.A.; Basher M.K.; Iftekharuzzaman; Kiong T.S.; Das N. (Institute of Electrical and Electronics Engineers Inc., 2024)
This research focuses on simulation studies that explore innovative approaches to energy conservation to empower remote areas through the implementation of sustainable power solutions. The objective is to address the energy needs of underserved regions that lack access to conventional power grids. By utilizing simulation techniques, this study aims to predict, analyze, and model various strategies for achieving the best and most cost-effective pathways of energy conservation and sustainable power generation in remote areas. This study assesses the performance, feasibility, and potential impact of each approach in terms of energy efficiency, cost-effectiveness, and environmental sustainability. The results of the simulation studies highlight the potential benefits of innovative energy conservation strategies in remote areas, including reduced energy costs, improved energy access, and enhanced socio-economic development. Furthermore, the research sheds light on the challenges and opportunities associated with the adoption and implementation of these approaches, guiding for overcoming barriers and maximizing the impact of sustainable power solutions. 2023 IEEE.